Kontribusi Parent-Child Attachment terhadap Regulasi Emosi, Harga Diri, Konformitas dan Resiliensi Siswa - Muarifah, Alif; Fauziah, Mufied; Saputra, Wahyu Nanda Eka (Jurnal Kajian Bimbingan dan Konseling, 2020)
This study aims to determine the contribution of parent-child attachment on emotion regulation, self-esteem, conformity and student resilience of students. To achieve the goal, the study applied a causal relationship study design. 153 subjects were chosen randomly from public junior high schools in Yogyakarta. The research data were collected using Attachment Scale, Emotion Regulation Scale, Self-Esteem Scale, Conformity Scale and Resilience Scale which had been tested for their validity and reliability. To analyze the data, this study used simple linear regression analysis. The findings showed that attachment has a significant contribution to emotion regulation, self-esteem, conformity and resilience with beta coeficient of 0.691, 0.816, 0.687 and 0.232.